ANALISIS KADAR NITROGEN PADA PUPUK UREA, PUPUK CAIR DAN PUPUK KOMPOS DENGAN METODE KJELDAHL - Yusmayani, Milis (Department of Chemistry, Faculty of Science and Technology, UIN Ar-Raniry, 2019)
This study aims to quantify the nitrogen level in the three different forms of fertilizer product: urea, compost, and liquid fertilizer manufactured by local Acehnese companies and compare it to the Indonesian National Standard (SNI) 19-7030-2004. All samples were analysed by using Kjeldahl method which consists of three steps: destruction, distillation, and titration. The analysis shows that the concentration of nitrogen in the urea, compost, and liquid fertilizer is 46.04; 2.79, and 0.0360% respectively. The results indicates that, when the data were compared to the value of nitrogen level in the SNI, both urea and compost are qualified to be released to national market. However, since the content of nitrogen in the liquid product is below the SNI, the latter fertilizer might not be considered as a qualified product in the term of nitrogen level.